Polyostotic Langerhans cell histiocytosis presenting as halitosis in a 24-year-old man: a case report - Hassan Mirmohammad Sadeghi; Sanaz Gholami Toghchi; Fatemeh Mashhadiabbas; Milad Baseri; Maryam Mohammadalizadeh Chafjiri; Parnian Nikraftar; Ardeshir Khorsand (Journal of Medical Case Reports)
Abstract Background Langerhans cell histiocytosis is a rare disease of the reticuloendothelial system. This report presents a novel case of Langerhans cell histiocytosis with systemic involvement that started with a simple chief complaint. The reporting of this case raises awareness of the distinctive characteristics of this challenging disorder. Case presentation A 24-year-old male patient of Persian ethnicity presented with a chief complaint of halitosis following coronavirus disease 2019 recovery to his general dentist’s office. Intraoral and extraoral examinations revealed no specific problem. In the follow-up session after phase I periodontal treatment, teeth sensitivity to cold stimulus was evident, and radiographs revealed a large lytic intraosseous lesion in the mandible. An incisional biopsy revealed Langerhans cells and a positive reaction to Langerin and cluster of differentiation 1a, thus, he was diagnosed with Langerhans cell histiocytosis. After performing positron emission tomography with fluoro-2-deoxyglucose and computed tomography, magnetic resonance imaging, and cone beam computed tomography, owing to generalized disease involvement, the patient was referred to an oncologist. Ultimately, it was found that the patient’s childhood health issues, including endocrine problems, were likely caused by an undiagnosed Langerhans cell histiocytosis. The oncologist chose denosumab, vinblastine, etoposide, 6-mercaptopurine, methotrexate, and pegfilgrastim regimen. The follow-up was not possible as the patient died following an accident. Conclusion This reveals the vitality of the early diagnosis of Langerhans cell histiocytosis to prevent disease progression. Awareness of diverse and nonpathognomonic manifestations of Langerhans cell histiocytosis, proper medical interview and history taking, and the use of routine radiographs may aid clinicians in lowering morbidity and mortality rates associated with such conditions.